Vérité prophétique et vérité philosophique dans l’œuvre de Rabbi Josef Ibn Caspi - Sadik, Shalom (Bulletin de Philosophie Médiévale, 2017)
Abstract The aim of this article is to analyze the opinion of a Jewish Averroist Rabbi Josef Ibn Caspi (Provence and Spain 1260-1345) on the relation between prophetical and philosophical truth. In the beginning of the article, we will see that in some of his writings, R. Caspi claims the prophet’s knowledge to be superior to that of the philosopher. However, in the second part of the article, we will analyze his commentary on Maimonides Guide of the Perplexed. In this commentary R. Caspi also mentions the opposite opinion: that the knowledge of the prophet is only his knowledge as a philosopher and that even true prophets’ (Ezekiel and Zakary) can have a few false prophecies just as good philosophers may have a few wrong opinions. He thus equates the knowledge of a prophet to that of a philosopher. In the conclusion of the article we try to determine how one can distinguish between the texts that explain the true opinion of R. Caspi and the text that our author wrote only for political and pedagogical reasons.